Distance to Neurovascular Bundle During Iliotibial Band Acl Graft Passage: A Cadaveric Study. Issue 5 (31st May 2022) - Thomas, Nicholas; Sanchez, Mark; Gupta, Anshal; Rohde, Matt; Ayala, Sal; Tompkins, Marc; Wilson, Phil; Ellis, Henry; Sherman, Seth; Green, Daniel; Ganley, Ted; Shea, Kevin G
Background: For patients with significant growth remaining, the Micheli-Kocher (iliotibial band) ACL reconstruction technique has proven to be a reliable procedure with minimal risk for growth disturbance. Recent cadaveric studies have demonstrated that graft passage over the top of the femur may bring the graft and instrument close to the critical neurovascular structures. Purpose: The purpose of this study was to evaluate the over-the-top graft passage technique using pediatric cadaveric knees, and measure the distance between instruments and the peroneal nerve, tibial nerve, popliteal artery. Methods: Seventeen skeletally immature cadaveric knees between the ages of 4 and 12 years old were dissected and prepared for visualization of iliotibial band graft passage procedure. A curved hemostat clamp was used, creating a path through the posterior capsule. To avoid neurovascular injury, the tip of the instrument was kept close to the posterior and lateral cortex of the femur. Once the clamp was safely positioned in the posterior knee joint, photographs were taken. Digital imaging software was used to measure the distance in centimeters from clamp tip to peroneal nerve laterally, and the popliteal artery and tibial nerve medially for all specimens, FIGURE 1. Distances were averaged and stratified to assess differences in age, FIGURE 2. Results: The average distances from clamp to neurovascular bundle were 0.875cm (range: 0.468-1.737cm), 0.968cm (range: 0.312-1.819cm), and 1.149cm (range: 0.202-2.409cm) for tibial nerve, popliteal artery and peroneal nerve, respectfully. Means were further calculated for age groups ≤8, 9-10, and 11-12 years old. Conclusion: Iliotibial band graft ACL reconstruction is one of the best options in the skeletally immature, as it has the lowest risk of growth plate complications and growth arrest. The neurovascular structures are very close to the path for over-the-top graft clamp placement with distances <1 cm in many subjects. The current study provides detailed measurements of instrument proximity to the neurovascular bundle in the posterior compartment of the knee. This knowledge is important to help surgeons who perform the Micheli-Kocher pediatric ACL reconstruction avoid damage to the nerves and vessels in this region. Careful instrument and graft passage, with awareness of proximity to critical structures, are important to reduce the risk of neurovascular injury. Figure 1. Measurements (cm) from clamp tip to neurovascular bundle in right knee model. Figure 2. Average distance from surgical instrument to neurovascular bundle are identified with respect to age.